WORKPLACE SMOKING RESTRICTIONS: COMMUNICATIONS AND LOBBYING SUPPORT PROGRAM (Tufts Archival Research Center, 2007)
Report on workplace smoking restrictions. Claims that public smoking restrictions fall into three broad categories; legislation, voluntary and litigation. Provides a list of resources, either currently available to yet to be made available, and a list of legislative and voluntary strategies. Concludes with a copy of the budget.